2019
DOI: 10.1364/ao.58.007392
|View full text |Cite
|
Sign up to set email alerts
|

All-optical switch and logic gates based on hybrid silicon-Ge2Sb2Te5 metasurfaces

Abstract: We numerically propose an all-dielectric hybrid metamaterial (MM) to realize alloptical switch and logic gates in shortwave infrared (SWIR) band. Such MM consists of one silicon rod and one Ge2Sb2Te5 (GST) rod pair. Utilizing the transition from amorphous to crystalline state of GST, such MM can produce electromagnetically induced transparency (EIT) analogue with active control. Based on this, we realized all-optical switching at 1500 nm with a modulation depth 84%. Besides, three different logic gates, NOT, N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…60 Particularly, a few works have numerically illustrated that the chalcogenide metasurfaces may lead to tunable EIT. [61][62][63] Following these theoretical predictions, the concept of tunable EIT was experimentally verified in a very recent work, which showed that a chalcogenide metasurface can be used to obtain a nonreversible switching of EIT via a thermal annealing system. 64 These previous works showed the promising potential of chalcogenide PCM in reconfigurable EIT metadevices in the optical region.…”
Section: Introductionmentioning
confidence: 90%
“…60 Particularly, a few works have numerically illustrated that the chalcogenide metasurfaces may lead to tunable EIT. [61][62][63] Following these theoretical predictions, the concept of tunable EIT was experimentally verified in a very recent work, which showed that a chalcogenide metasurface can be used to obtain a nonreversible switching of EIT via a thermal annealing system. 64 These previous works showed the promising potential of chalcogenide PCM in reconfigurable EIT metadevices in the optical region.…”
Section: Introductionmentioning
confidence: 90%
“…However, because it is based on metallic metamaterials, high loss of metal increases the device loss and high conductance of metal weakens the thermal accumulating for the transition process, which may have negative effect on the device switching speed ( Kuznetsov et al., 2016 ). Recently, the tunable all-dielectric metasurface has been explored ( Staude et al., 2018 )( Sautter et al., 2015 ) and used in all-optical switches ( Zhang et al., 2019 ). However, most of the previous studies are based on nano-grating structure, which is sensitive to polarization ( Karvounis et al., 2016 )( Gholipour et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The GST calcogenide phase change materials, (so this includes GeTe), can be quickly [9] and repeatedly [10] switched between amorphous and crystalline states by appropriate thermal, electric, or optical stimuli [11][12][13]. Until now, GST chalcogenides have been regarded as strong candidates for realizing reconfigurable and nonvolatile all-optical devices [14], and many applications have been proposed, such as all-optical switching [15], optical filter [16], and reconfigurable metasurfaces [17,18]. Plasmonic absorbers based on PCMs including GeTe were analyzed in in [19][20][21], this resonant structures composed by metals and PCM's as insulators with sub-wavelength dimensions have been used as mirrors to suppress transmission by increasing the reflection and inducing destructive interference from reflected light at resonant wavelengths absorbed on the structure [22].…”
Section: Introductionmentioning
confidence: 99%